NEUROINFLAMMATION IN ALZHEIMER’S DISEASE AND INVOLVEMENT OF INTERLEUKIN-1: A MECHANISTIC VIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Ageing is a universal biological fact and a natural process. It begins from the day we are born, or perhaps even before. Of the world’s 580 million elderly, 77 million (22% of total) live in India. The increasing life expectancy of Indians, in the last decade, is likely to result in an increase in age-related disorders like Alzheimer’s disease and Parkinson’s disease. Alzheimer’s disease, the most common disorder of geriatric population, is a chronic, progressive, untreatable neurodegenerative disorder characterized by apraxia, aphasia, agnosia and severe cognitive deficits. Several behavioural changes like anxiety, hallucinations, depression and delusions are also experienced. Lot of progress has been made regarding understanding the pathological pathways involved, yet the available therapy only provide symptomatic relief but do not stop progression of disease. Several of key areas have been recognised and out of them inflammation has been regarded as inseparable and crucial factor involved. Interleukin-1 is a key molecule in systemic immune responses in health and disease and has analogous roles in the brain where it contributes to neuronal degeneration by energy dysfunction and triggering production of other cytokines, nitric oxide and others. IL-1 over expression is also associated with rheumatoid arthritis, vascular dementia, diabetes mellitus, periodontitis, systemic sclerosis, autoimmune encephalomyelitis and cerebral infarction. Present review is an effort to present IL-1 as potential therapeutic target in treatment of Alzheimer’s disease by linking it with several of pathological factors like amyloidβ, neurofibrillary tangles, neuron loss and cholinergic dysfunction.